2014
DOI: 10.1097/ico.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Transient Interface Fluid on Intraoperative OCT and Textural Interface Opacity After DSAEK Surgery in the PIONEER Study

Abstract: Purpose To examine the association between transient interface fluid (TIF) and textural interface opacity (TIO) following DSAEK surgery using intraoperative optical coherence tomography (iOCT) in the PIONEER study. Methods All consecutive eyes that underwent DSAEK between October 2011 and September 2013 from the PIONEER intraoperative and perioperative OCT study were included. iOCT images were captured after lenticule apposition with complete air fill and after air-fluid exchange. Postoperative day (POD) 1 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 11 publications
0
44
0
3
Order By: Relevance
“…5,6,9,14,15 In our study, the continuous feedback provided by the microscope-integrated iOCT helped in the assessment of the completion of DM scoring, the orientation of the unfolded graft, position of the incision, the relationship of the incision and graft edge, and the position and stability of the IOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,9,14,15 In our study, the continuous feedback provided by the microscope-integrated iOCT helped in the assessment of the completion of DM scoring, the orientation of the unfolded graft, position of the incision, the relationship of the incision and graft edge, and the position and stability of the IOL.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Intraoperative optical coherence tomography (iOCT) is an emerging entity with potential benefits in both anterior and posterior segment surgeries. [5][6][7][8][9][10][11] It has the potential to increase our understanding of the tissue alterations that occur during surgical manipulations. We herein evaluated the role of microscope-integrated iOCT to assess the time to donor apposition in cases undergoing Descemet stripping automated endothelial keratoplasty (DSAEK).…”
mentioning
confidence: 99%
“…9,12,13,22,23,27,29,32,39,41,42 Using intraoperative OCT surgeons are able to obtain immediate feedback on the status of the surgical procedure.…”
Section: Anterior Segmentmentioning
confidence: 99%
“…In fact, residual subclinical interface fluid at the end of the case has been associated with postoperative textural interface opacity. 39 In the DISCOVER study, intraoperative OCT findings resulted in additional surgical maneuvers in 41% of patients. 27 In the PIONEER study, intraoperative OCT identified residual persistent fluid in 48% of eyes that resulted in additional surgical maneuvers.…”
Section: Anterior Segmentmentioning
confidence: 99%
See 1 more Smart Citation